1962
DOI: 10.1192/bjp.108.452.101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Depression and the Response to Imipramine (“Tofranil”)

Abstract: Since it was first reported by Kuhn in 1957, the value of imipramine in the treatment of depressive illness has become generally recognized and confirmed by clinical trials (Blair, 1960; Daneman, 1961; Rees et al., 1961). It continues to hold an important place in therapy despite the introduction of many other antidepressant drugs and the occasional adverse report (Ashby & Collins 1961). Nevertheless the indications for its use are by no means established. It has been claimed that certain types of depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Sargant (1967) has suggested that members of the imipramine group are useful in endogenous and MAOT groups in neurotic depression. These observations have been confirmed by many (Ayd, 1959;Blair, 1960;Friedman, DeMowbray and Hamilton, 1961;Greenblatt, Grosser and Weschsler, 1962;Keup et al, 1960;Kiloh, Ball andGarsidè, 1962, Lehmann, 1965) while others have failed to confirm Kuhn's original finding (Abraham et al, 1976;Fleminger and Görden, 1962, Rees et al, 1961, and Spear et al, 1964. The diagnostic criteria of endogenous depression have not been spelled out in most instances and thus predictive value is lost.…”
Section: Endogenous-neuroticmentioning
confidence: 60%
“…Sargant (1967) has suggested that members of the imipramine group are useful in endogenous and MAOT groups in neurotic depression. These observations have been confirmed by many (Ayd, 1959;Blair, 1960;Friedman, DeMowbray and Hamilton, 1961;Greenblatt, Grosser and Weschsler, 1962;Keup et al, 1960;Kiloh, Ball andGarsidè, 1962, Lehmann, 1965) while others have failed to confirm Kuhn's original finding (Abraham et al, 1976;Fleminger and Görden, 1962, Rees et al, 1961, and Spear et al, 1964. The diagnostic criteria of endogenous depression have not been spelled out in most instances and thus predictive value is lost.…”
Section: Endogenous-neuroticmentioning
confidence: 60%
“…It describes a commonly recurring structure of communicating components that solves a general design problem within a particular context." [21]. Patterns solve a specific problem but are neutral or have weaknesses with respect to other qualities.…”
Section: Strategiesmentioning
confidence: 99%
“…The third approach is based on the concept of "pattern", described for the first time in architecture by Alexander, Ishikawa, and Silverstein (1977), then promoted in software engineering by Gamma et al (1993) and Bushmann, Meunier, and Rohnert (1996). In the field of systems engineering, Barter (1998) and Haskins (2003), were the first to introduce pattern and pattern language for capturing the engineering knowledge.…”
Section: State Of the Art Of Knowledge Reusementioning
confidence: 99%
“…But, facing the increasing complexity of systems, difficulties emerge to formalize expert know-how, making it laborious to reuse (or at a great cost of energy, time, and money). To deal with this complexity, MBSE has been introduced to shift the document-centric approach practiced by engineers towards a model-centric approach, that "integrates system requirements, design, analysis, and verification models to address multiple aspects of the system in a cohesive manner" (Friedenthal, Moore, and Steiner 2008). One consequence of this formalized application of modeling is opening the way to search new forms of expressible and reusable knowhow to improve engineering activities.…”
mentioning
confidence: 99%